The impact of farmers' field schools weekly training on the adoption of some recommended wheat cultural practices by Gezira scheme tenants - Hag Khalifa, El Badawi K.; Hussein, Mohmmed B.; Babikir, Osman A. (Gezira Journal of Agricultural Science; Vol 5 No 2 (2007), 2007)
The objective of this study was to determine the influence of weekly participation of Gezira scheme tenants in training sessions in farmers'  field schools (FFSs) on adoption of some recommended wheat cultural practices. Tenants weekly participation in training sessions in FFSs was considered an independent variable, while adoption of recommended urea and phosphorus application  and their doses , watering interval  and  sowing date were considered dependent variables. A sample of 80 farmers were selected to answer a prepared questionnaire of whom 40 participated in the FFSs weekly training and 40 did not .The adoption of recommended water intervals ,urea dose and application and phosphorus application were dependent on FFSs weekly training sessions, while  adoption  of the  recommended  sowing  date  and phosphorus dose were not  dependent on the FFSs weekly training sessions. It was  recommend that FFSs approach to be continued and at a higher scale, also field personnel of the Gezira scheme should train farmers through this appro-ach in problem- solving techniques in order to encourage  more farmers' participation in extension activities which would lead  to higher rates of adoption of the recommended cultural practices.